Evaluation of the total phenol content and antioxidant potential of plant extract (Plumeria alba) - Mohamad Nor, Maryana; Zuberdi, Ahmad Muzammil; Omar, Muhammad Nor (Academic Information Press, 2012)
The total phenol content (TPC) and antioxidant activities of methanol extracts from aerial parts of P.alba were studied. The results showed that stem bark contained the highest level of total phenols (7.17 ± 0.1947 mg GAE/g) while the lowest level was obtained from the flower (6.00 ± 0.244 mg GAE/g). The IC50 value of BHT (control) was 22.6 ± ug/ml and the values from the extract of stem bark, leaf and flower were 22.3 ± 2.71, 25.9 ± 0.23 and 30.1 ±2.23 ug/ml respectively. These results indicated that stem bark exhibited the higestr antioxidant activity compared to other plant part and almost similar with the control (BHT). A medium correlations were found between total phenols and free radical scavenging capacities in tested extracts by DPPH system ((R2 = 0.605)